2012
DOI: 10.1128/iai.05530-11
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Exposure to Aspergillus fumigatus Conidia Results in CD4+T Cell-Dependent and -Independent Pulmonary Arterial Remodeling in a Mixed Th1/Th2/Th17 Microenvironment That Requires Interleukin-4 (IL-4) and IL-10

Abstract: Pulmonary arterial remodeling is a pathological process seen in a number of clinical disease states, driven by inflammatory cells and mediators in the remodeled artery microenvironment. In murine models, Th2 cell-mediated immune responses to inhaled antigens, such as purified Aspergillus allergen, have been reported to induce remodeling of pulmonary arteries. We have previously shown that repeated intranasal exposure of healthy C57BL/6 mice to viable, resting Aspergillus fumigatus conidia leads to the developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 54 publications
4
31
0
Order By: Relevance
“…Increased T H 1, T H 2, T H 17, and T reg cells are present during peak inflammation (34). We have also found that IL-10 knockout mice have a defective T H 2 response to challenge with A. fumigatus conidia (56). Since IFN-␥ can also regulate the development of T H 17 cells (11), we examined whether IL-10, IFN-␥, or IL-4 play a role in regulating the development of T H 17 cells in the lungs of mice exposed to A. fumigatus conidia, using cytokine-specific knockout mice.…”
Section: Roles Of Ifn-␥ Il-4 and Il-10 In The Development Of T H 17mentioning
confidence: 51%
See 3 more Smart Citations
“…Increased T H 1, T H 2, T H 17, and T reg cells are present during peak inflammation (34). We have also found that IL-10 knockout mice have a defective T H 2 response to challenge with A. fumigatus conidia (56). Since IFN-␥ can also regulate the development of T H 17 cells (11), we examined whether IL-10, IFN-␥, or IL-4 play a role in regulating the development of T H 17 cells in the lungs of mice exposed to A. fumigatus conidia, using cytokine-specific knockout mice.…”
Section: Roles Of Ifn-␥ Il-4 and Il-10 In The Development Of T H 17mentioning
confidence: 51%
“…Similarly, there is a significant reduction in the percentage of CD4 ϩ CD25 ϩ FoxP3 ϩ T cells and a lower rate of CD4 T cell activation. We have previously shown that IL-10 Ϫ/Ϫ mice develop far less inflammation following four challenges than WT mice and do not develop pulmonary eosinophilia or T H 2 cells (56). It is therefore possible that IL-17 plays not only a direct role in promoting pulmonary eosinophilia and cellular accumulation during the allergic response but has a central, albeit subtle, role in shaping the initial immune response itself.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The importance of studying infection with live organisms is emphasized by the profile of the inflammatory response seen in mice colonized with Af beads, which differed from those challenged with conidia in suspension and from repeated challenge with conidia or other models that used sensitized mice (23,29). First, colonization with A. fumigatus hyphae resulted in only a modest Th2-type response early in infection.…”
Section: Discussionmentioning
confidence: 99%